Viscosity measurements of compressed liquid dipropyl and dibutyl adipates - Diogo, João C. F. (2016)
The paper reports viscosity measurements of compressed liquid dipropyl (DPA) and dibutyl (DBA) adipates obtained with two vibrating wire sensors developed in our group. The vibrating wire instruments were operated in the forced oscillation, or steady-state mode. The viscosity measurements of DPA were carried out in a range of pressures up to 18. MPa and temperatures from (303 to 333). K, and DBA up to 65. MPa and temperature from (303 to 373). K, covering a total range of viscosities from (1.3 to 8.3). mPa. s. The required density data of the liquid samples were obtained in our laboratory using an Anton Paar vibrating tube densimeter and were reported in a previous paper. The viscosity results were correlated with density, using a modified hard-spheres scheme. The root mean square deviation of the data from the correlation is less than (0.21 and 0.32)% and the maximum absolute relative deviations are within (0.43 and 0.81)%, for DPA and DBA respectively. No data for the viscosity of both adipates could be found in the literature. Independent viscosity measurements were also performed, at atmospheric pressure, using an Ubbelohde capillary in order to compare with the vibrating wire results. The expanded uncertainty of these results is estimated as ±1.5% at a 95% confidence level. The two data sets agree within the uncertainty of both methods. © 2015 Published by Elsevier B.V.